2007
DOI: 10.1016/j.chroma.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of chlorophenols in environmental water samples by hollow fiber supported ionic liquid membrane extraction coupled with high-performance liquid chromatography

Abstract: The 1-octyl-3-methylimidazolium hexafluorophosphate ([C 8 MIM][PF 6 ]) ionic liquid was immobilized in the pores of a polypropylene hollow fiber for hollow fiber-protected liquid-phase microextraction. Analytes including 4-chlorophenol (4-CP), 3-chorophenol (3-CP), 2,4-dichlorophenol (2,4-DCP) and 2,4,6-trichlorophenol (2,4,6-TCP) were extracted into this ionic liquid membrane, and back extracted into 10 L sodium hydroxide acceptor solution in the lumen of the hollow fiber. Then, the acceptor solution was with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(85 citation statements)
references
References 26 publications
(28 reference statements)
1
84
0
Order By: Relevance
“…Furthermore, the abundance of Actinobacteria may be affected by the abundance of humic substances in water samples. It has been reported that humic acid concentrations range from 0 to 50 mg/L in most environmental surface waters (Peng et al 2007). Actinobacteria may be related to the consumption of humic substances, which plays a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the abundance of Actinobacteria may be affected by the abundance of humic substances in water samples. It has been reported that humic acid concentrations range from 0 to 50 mg/L in most environmental surface waters (Peng et al 2007). Actinobacteria may be related to the consumption of humic substances, which plays a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using 1-hexyl-3-methylimidazolium tetrafluoroborate in temperature-controlled dispersive liquid-phase microextraction pyrethroid pesticides (Zhou et al, 2008) were isolated from aqueous solution. Headspace liquid-phase microextraction using 1-octyl-3-methylimidazolium hexafluorophosphate was applied for extraction of halomethanes, alkyl aromatic compounds (Aguilera-Herrador et al 2008a,b, 2009, and chlorophenols (Peng et al, 2007). 1-Butyl-3-methylimidazolium hexafluorophosphate enabled the separation of chlorobenzenes and chloroanilines (Vidal et al, 2007).…”
Section: Liquid-liquid Extraction By Hydrophobic Ionic Liquidsmentioning
confidence: 99%
“…The current drinking water guideline values in the US for 2-CP and 2,4-DCP are 0.1 and 0.5 μg/L, respectively (Pera-Titus et al 2004). The EU has set target limits in drinking water of 0.5 and 0.1 μg/L for total content of chlorophenols and individual ones, respectively (Peng et al 2007;Elci et al 2011).…”
Section: Responsible Editor: Philippe Garrigues Submitted To: Environmentioning
confidence: 99%